Zirconia foams prepared by integration of the sol-gel method and dual soft template techniques - Rosa, M. A. Alves [UNESP]; Santos, E. P. [UNESP]; Santilli, Celso Valentim [UNESP]; Puldnelli, S. H. [UNESP] (Elsevier B.V., 2008)
This paper presents a new method to produce basic zirconium sulfate foams showing hierarchic porosity, based on a dual pores templating process by oil drops and gas bubbles dispersed into a hydrosol, followed by its fast gelation to form the porous patterned inorganic network. As revealed by mercury porosimetry, the hierarchical structures of final inorganic foams are composed by large gas bubble templated macropores (modal size 7-33 mu m) and emulsion-templated supermeso-pores of modal size tunable around 3 and 0.4 pm. The relative population and modal pore size of each family and the overall porosity of the final inorganic foam can be varied by adjusting the emulsification and air-liquid foaming stirring speed, and the oil/sol ratio. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Micelles; Porosity; Sol-gel, aerogel and solution chemistry